The energy-absorbing characteristics of single spherical-roof contoured-core (SRCC) cell with composite materials - Quanjin, Ma; M. R. M., Rejab; Kang, Shaofu; Idris, Mat Sahat; M.A.A., M. Zin (Universiti Malaysia Pahang, 2020)
It is a challenging task to manufacture the novel lightweight sandwich panel with different composite materials. The aim of this paper is to study the energy-absorbing characteristics of single spherical-roof contoured-core cell with carbon, glass and aramid fibre reinforced plastics, which were fabricated through compression moulding technique. The quasi-static compression test was carried out to investigate the compressive properties and crushing behaviour of the single contoured-core cell. It was demonstrated that the single spherical-roof contoured-core with aramid fibre reinforced plastic provided the highest specific energy absorption value of 0.69 kJ and the lowest compressive stiffness of 30.43 kN/mm compared to carbon and glass fibre reinforced plastics. Furthermore, it was observed that matrix cracks, fibre fracture and laminate bending are the main failure modes of the single contoured-core cell under quasi-static loading.